Preparation of modified CdSe/ZnS quantum dots and gold nanoparticles for glucose and dengue detection - Abd. Rahman, Samsulida (2018)
Development of sensors combined with nanomaterials becoming an interesting area due to their unique optical properties. In this research, two different biosensor utilizing CdSe/ZnS quantum dots (QDs) and gold nanoparticles (AuNPs) have been developed and successfully applied to detect glucose and dengue virus DNA, respectively. CdSe/ZnS QDs is utilized in our first prepared biosensor for glucose monitoring. The CdSe/ZnS QDs was successfully prepared via hot injection method while the ZnS layer was made using the successive ionic layer adsorption and reaction (SILAR) method. The prepared QDs was spherical monodisperse with uniform sizes of 3 to 3.2 nm and 10 to 12 nm for CdSe core QDs and CdSe/ZnS core-shells QDs, respectively. The prepared CdSe/ZnS QDs has been modified with organic ligand for glucose analysis. Detection was performed using glucose concentrations ranging from 0 to 40 mM with linear relationship was observed from 0 to 10 mM (with R2 = 0.9964) and limit of detection was obtained at 0.3 mM. Comparison between our developed biosensor with commercialized assay kit result in 99% similarity thus indicated that the developed biosensor utilizing CdSe/ZnS QDs was reliable for the detection of glucose. AuNPs is utilized in our second prepared biosensor for dengue virus detection. Positively charged AuNPs was interacting with negatively charged PNA/DNA hybridised biochip via electrostatic interaction and successfully used to detect dengue virus using both naked eye and optical scanner. Detection of dengue virus was study using concentration ranging from 10 pM to 1 μM with a detection limit was obtained at 10 pM. Repeatability and reproducibility study gave relative standard deviations (RSD) less than 5% in all measurements, which indicate that the chips produced in this study are suitable for mass fabrication of devices with similar responses. Comparison study between our developed PNA/DNA biochip with real time RT-PCR was investigated and obtaining 88% agreement. Both scopes covered in this study give new possibilities for healthcare monitoring, where these studies improved the specificity and selectivity of the developed biosensor.